A First Year Medical Student’s Perspective on Working in ICU during the COVID-19 Pandemic - Erin McCabe (International Journal of Medical Students, 2020)
The COVID-19 pandemic has brought forth unprecedented times. Due to this, medical students of all abilities and competencies can play a meaningful part in patient’s treatment.   Throughout medical school, teaching is focussed on the overarching clinical care needed – from medication to surgery. However, there are many other aspects of care required for patient’s recovery, such as personal care. Working as a healthcare assistant brings this to the forefront, particularly in an intensive care unit, during a pandemic. This allowed me to experience a different side of medicine and patient care, something I believe all medical students should see.